Variables associated with pediatric emergency department visits for uncontrolled pain in postoperative adenotonsillectomy patients. (August 2019) - Lavin, Jennifer; Lehmann, David; Silva, Astrid Leon; Bai, Guangyu; Hebal, Ferdynand; Manworren, Renee; Stake, Christine; Rychlik, Karen; Billings, Kathleen R.
Abstract: Objective: Returns to the emergency department (ED) for pain or dehydration after adenotonsillectomy (T&A) are frequent. Attempts to associate the specific pain regimens with these visits have been unrevealing, suggesting a need to assess for other potential factors associated with readmission. Methods: A review of a 2:1 cohort matched by age, gender and payer status compared post-T&A patients who did not return ED for pain or dehydration within 21 days to those who returned. Factors investigated included patient demographics, comorbidities, medication regimen and the presence of postoperative telephone encounters. Patients returning to the ED were further assessed for rates of medication adherence. Results: 7493 patients underwent T&A during the period. Of these, 144 (1.9%) returned for pain/dehydration. Comparison to 285 matched patients revealed an association between ED returns and Hispanic ethnicity ( p < 0.001), Spanish language ( p = 0.0002), and comorbid Down syndrome and ADHD ( p = 0.011 in both). The incidence of parent telephone calls to the office was associated with ED returns (58.7 in the ED cohort, 28.4% in non-ED cohort, p < 0.0001). On multivariable analysis, Hispanic ethnicity and phone calls were associated with ED returns ( p < 0.0001 and p < 0.0001, respectively). Only 64.0% of patients returning to the ED were adherent with postoperative pain regimens. Conclusions: While demographic factors may be associated with rate of ED returns for pain and dehydration, post-operative phone calls were most highly associated with returns. The majority of patients returning to the ED were non-adherent with recommended pain regimens, suggesting an opportunity to investigate medication adherence in all post-tonsillectomy patients.